Concentration Of Micronutrient (Fe, Cu, Mn) In Cocoa Plantation Land In Transmigration Area, East Luwu Regency - Felycitae Ekalaya Appa; Yunita Pare Rombe; Dewi Lidiawati (J-HEST Journal of Health Education Economics Science and Technology, 2022)
Micronutrients such as Fe, Cu and Mn function to help maintain land productivity, improve soil fertility that has been lost, and increase crop production. Micronutrients are also required for metabolic activity and growth in cocoa plants. Therefore, it is necessary to pay attention to the micronutrient content in the soil where cocoa plants grow. The purpose of this study was to determine the content of micronutrients (Fe, Cu, and Mn) in regional plantation soils. The analysis method uses Inductively Coupled Plasma. The results showed that the micronutrient content in cocoa soil with 5 locations was Iron (Fe), Copper (Cu), and Manganese (Mn) with an average of 1056.050 mg/100g; 3.816 mg/100g; and 53.350 mg/100g.